2015
DOI: 10.3945/ajcn.114.104273
|View full text |Cite
|
Sign up to set email alerts
|

Association of coffee intake with total and cause-specific mortality in a Japanese population: the Japan Public Health Center–based Prospective Study

Abstract: With this prospective study, we suggest that the habitual intake of coffee is associated with lower risk of total mortality and 3 leading causes of death in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 35 publications
5
40
1
1
Order By: Relevance
“…The subjects in this study were participants in other investigation trials, potentially introducing selection bias. It was reported that participants with higher coffee consumption smoked more (29,30), and smokers showed the highest intake of total polyphenols in Europe (11). In our study, the energy-adjusted polyphenol intake in smokers was slightly higher than in non-smokers, but the number of smokers was not high enough to analyze CVw, coefficient of within-individual variation; CVb, coefficient of between-individual variation; VR, within-to betweenindividual variance ratio.…”
Section: Discussioncontrasting
confidence: 59%
“…The subjects in this study were participants in other investigation trials, potentially introducing selection bias. It was reported that participants with higher coffee consumption smoked more (29,30), and smokers showed the highest intake of total polyphenols in Europe (11). In our study, the energy-adjusted polyphenol intake in smokers was slightly higher than in non-smokers, but the number of smokers was not high enough to analyze CVw, coefficient of within-individual variation; CVb, coefficient of between-individual variation; VR, within-to betweenindividual variance ratio.…”
Section: Discussioncontrasting
confidence: 59%
“…The main outcomes were all‐sites cancer incidence and mortality. We used the International Classification of Diseases, 9th revision (ICD‐9), for data between 1983 and 1994, and the 10th revision (ICD‐10), for data between 1995 and 2000, to classify the all‐sites cancer (ICD‐9, codes 140–208; ICD‐10, codes C00–C97) …”
Section: Methodsmentioning
confidence: 99%
“…In this population, increasing coffee consumption resulted in a decreased risk of all-sites cancer incidence and mortality.C offee is one of the most widely consumed beverages (1) and almost 40% of adults drink coffee daily in Japan. (2,3) Coffee contains a number of bioactive compounds, (4) and its anti-inflammatory effect, mediated by caffeine and chlorogenic acid, is well recognized. (2,5) Research indicates that regular coffee consumption over a lifetime may have a beneficial effect for health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because Saito et al showed in another report (6) that coffee consumption was also inversely associated with mortality from heart disease, cerebrovascular disease, and respiratory disease in Japan, caffeine, which is one of the active substances in green tea, was suggested to produce health benefits. However, greater efforts have been put into the investigation of green tea catechins, in particular of epigallocatechin gallate (EGCG), which is the main gallate-type catechin in green tea.…”
mentioning
confidence: 99%